THE ROLE OF CLINICAL LABORATORY DIAGNOSTICS IN THE DIAGNOSIS OF INFECTIOUS DISEASES IN CHILDREN - Marufova Shaxzoda Furkatovna; Isomadinova Lola Kamolidinovna; Karimova Linara Alixanovna (Web of Journals Publishing, 2025)
Infectious diseases are a common cause of morbidity in pediatric populations, and accurate diagnosis is critical for effective treatment and management. Clinical laboratory diagnostics plays a crucial role in identifying the causative pathogens and understanding the severity of the infection. This article reviews various laboratory methods, including microbiological cultures, PCR, rapid antigen tests, and serological assays, which are commonly used to diagnose pediatric infections. The paper also discusses the role of these diagnostics in guiding therapeutic decisions and improving patient outcomes.
Keywords: Сlinical laboratory diagnostics, infectious diseases, pediatrics, PCR, microbiological cultures, serological tests, rapid antigen tests.